Altered polar character of nanoconfined liquid water - Sayantan Mondal; Subhajit Acharya; Biman Bagchi (Physical Review Research, 2019)
Atomistic molecular dynamics simulation study of dipolar fluids confined to spherical nanocavities of radii ranging from R_{c}=1 to 4 nm reveals a surprisingly small Kirkwood correlation factor (g_{K}) in water, but not so in dipolar Stockmayer fluid. This results in an ultrafast relaxation of the total dipole moment time correlation function (DMTCF) of water. The static dielectric constant of water under nanoconfinement exhibits a strong dependence on size with a remarkably low value even at R_{c}=3nm and a slow convergence to the bulk value because of surface-induced long-range orientational correlations. Interestingly, DMTCF exhibits a bimodal 1/f noise power spectrum.